Zuni Indian mission records
Three volumes containing a history and lists (from 1776) of births, deaths, and marriages at the Spanish mission to the Zuni Indians located in what is now New Mexico.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in Spanish.
Keywords: Missions, Spanish -- New Mexico; Zuni Indians; New Mexico -- History -- To 1848.; New Mexico -- History -- 1848-